Safety and immunogenicity of IMVAMUNE®, a third-generation vaccine based on the modified vaccinia Ankara (MVA) strain - L. F. Stovba; O. V. Chukhralya; N. K. Chernikova; A. L. Khmelev; S. V. Borisevich (Биопрепараты: Профилактика, диагностика, лечение, 2023)
In 1980, the World Health Assembly officially declared smallpox eradicated in the world, which allowed developed countries to stop preventive vaccination against this disease. However, circulating and emerging orthopoxviruses along with the lack of herd immunity prompt the need for emergency smallpox vaccines meeting the current requirements for biologicals.The aim of the study was to analyse the safety and efficacy of third-generation smallpox vaccines based on the MVA strain of vaccinia virus compliant with the current (stricter) immunogenicity and safety requirements in healthy subjects and especially in patients with underlying health conditions, considering the lack of herd immunity to orthopoxviruses.The authors analysed the existing experience with smallpox vaccines. The vaccines based on the modified vaccinia Ankara (MVA) strain hold a special place amongst other third-generation vaccines, as this strain is safe and can be used for creating vector vaccines. Bavarian Nordic produces the MVA-based vaccine under three brand names (Imvanex in the EU, Jynneos™ in the USA, and IMVAMUNE® in Canada). According to the results of MVA-based vaccine clinical trials in healthy volunteers and patients with various underlying conditions, the main mild adverse drug reactions (erythema, pain, pruritus, and swelling) were mostly registered at the injection site. The systemic adverse drug reactions included fatigue, headache, myalgia, and chills; several subjects developed upper respiratory tract infections, nausea, and gastroenteritis, which resolved spontaneously within a day. MVA-based vaccines did not cause any cardiac abnormalities, including myo- or pericarditis. Thus, the vaccines may be used in patients with eczema, atopic dermatitis, inflammatory skin conditions, HIV, tuberculosis, cardiac abnormalities, as well as in children, adolescents, and pregnant women. The optimal intradermal immunisation dose was 1×108 TCID50. Two injections at this dose induced a pronounced humoral and cell-mediated immune response comparable to that induced by one administration of a first-generation smallpox vaccine. At this dose, the study vaccine also boosted pre-existing immunity conferred by a first-generation vaccine. The US Centers for Disease Control and Prevention recommend Jynneos™ for preventing monkeypox in adults (18 years of age and older).